PENGARUH SELF-REGULATION TERHADAP ADIKSI PENGGUNAAN INSTAGRAM PADA PESERTA DIDIK - Arifin, Nurdin; Aurelin (SISTEMA: Jurnal Pendidikan, 2024)
With the advancement of technology in today's era, it is becoming increasingly sophisticated, with even many members of Generation Alpha being familiar with it. When it comes to using Instagram, the Alpha generation has shown signs of Instagram addiction by fulfilling the 7 aspects of social media addiction on Instagram. The Alpha generation should already possess self-regulation in order to prevent addictive behavior tendencies in their identity. Self-regulation is a key element that can help limit addictive actions. Hence, the goal of this study is to collect concrete information on how self-regulation impacts Instagram addiction. This study employed a quantitative methodology, specifically utilizing simple linear regression analysis on a sample of 80 fourth-grade students from SDN 003 Sungai Pinang. The tools used for measurement are the self-regulation scale and the Instagram addiction scale. The findings of this study indicate that self-regulation accounts for 27% of the variance in Instagram addiction, with the remaining 73% being attributed to other factors.